Class switched bovine ultralong CDR H3 amplicons versus canonical in immune and non-immune tissues - Karina L. Hissen; Morgan Sheppard; Jeannine A. Ott; Kerstin K. Landrock; Casey Whitley; Nicholas Ebert; J. M. Cody Horton; Nicole A. Glenn; Yoonsung Jung; Vaughn V. Smider; Michael F. Criscitiello (Immunogenetics, 2026)
Within the bovine immune response, a distinct type of immunoglobulin (Ig), known as ultralong complementarity-determining region 3 (CDR3) antibodies, coexists alongside canonical Igs. These ultralong heavy chains (HC) feature a remarkable structure with a lengthened CDR3 of the heavy chain (CDR H3), allowing them to adopt either a smaller and more extended paratope than canonical antibodies. However, very little is known about the distribution of ultralong CDR H3s in cattle tissues and which isotypes they are ultimately associated with. This study analyzed and quantified the amplicons of the five immunoglobulin isotypes (IgM, IgD, IgG, IgA, and IgE) for both the canonical and ultralong CDR H3 throughout 24 Bos taurus tissues. IgH amplicons analysis identified an extensive repertoire of expressed canonical and ultralong CDR H3s of each isotype in most tissues. Ultralong cattle Igs were preferentially switched to the IgG isotype, especially in the medial retropharyngeal lymph node draining the immunization site. Additionally, B cells producing canonical Igs in bone marrow switched most to the IgG isotype. These data suggest that ultralong CDR H3 may be uniquely qualified to handle some antigens. A more comprehensive understanding of isotype and tissue-specific immune responses of these unusual antibodies can provide a deeper insight into their function within the overall cattle immune system, offering unique opportunities for innovations for in both bovine health and human immunotherapeutics.

Recent Results on Science and Innovation Related to Electrical Processes of Thunderstorms - Christoph Köhn; Torsten Neubert; Martin Füllekrug; Ute Ebert; Sander Nijdam; Olivier Chanrion; Nikolai Østgaard; Martino Marisaldi; Serge Soula; Joan Montanyà; Francisco Gordillo-Vázquez; Alejandro Luque; et al. (Surveys in Geophysics, 2025)

Unveiling Macroecological Patterns of Elasmobranchs in the Eastern Pacific Ocean - Andrés F. Navia; Joanna Alfaro‐Shigueto; Jose Ágreda‐Arango; Elisa Areano; Cristopher Avalos‐Castillo; Joseph J. Bizzarro; Carlos Bustamante; Adriana Cevallos; Francisco J. Concha; Víctor H. Cruz‐Escalona; David A. Ebert; Mario Espinoza; et al. (Journal of Biogeography, 2025)
Aim To examine the species richness, distribution and macroecological patterns of elasmobranch assemblages across a broad latitudinal gradient in the Eastern Pacific Ocean (EPO). Location The study area encompasses the Pacific coast of the American continent, spanning from 65°N to 60°S, and extending from the coastline to approximately 1000 km offshore, encompassing the oceanic archipelagos. Taxon Elasmobranchs. Methods Utilising the established distribution ranges of 190 elasmobranch species (comprising 89 sharks and 101 rays), we assessed the richness and spatial distribution of these species across the EPO. Subsequently, three macroecological patterns were scrutinised: Rapoport's rule, the Mid Domain Effect with its association to Mean Sea Surface Temperature, and the correlation between body size and latitudinal distribution. Results The analysis of species richness along latitudinal gradients unveiled a bimodal pattern, reaching peaks between 30° to 20°N and 10°N to 5°S. A decline in species richness was observed from tropical to polar regions. Contrary to Rapoport's Rule, Stevens' and midpoint methods demonstrated higher geographic range values at lower latitudes, diminishing towards higher latitudes. Additionally, the mid‐domain effect model exhibited a robust correlation with the mean sea surface temperature. Exploring the interspecific relationship between body size and extent of occurrence, it was found that 29 out of 190 species are more susceptible to extinction. Main Conclusion Marine elasmobranchs of the EPO defy conventional latitudinal richness patterns and deviate from Rapoport's rule. Furthermore, our findings indicate a robust correlation between observed richness and both sea surface temperature and environmental heterogeneity. The proportion of species vulnerable to human or stochastic impacts potentially leading to extirpation in relation to their geographic range was low across the majority of examined provinces.

Spatial extent and isolation of marine artificial structures mediate fish density - Virginia A. Gilliland; Avery E. Fessler; Avery B. Paxton; Erik F. Ebert; Ryan M. Tharp; Brendan J. Runde; Nathan M. Bacheler; Jeffrey A. Buckel; J. Christopher Taylor (Frontiers in Marine Science, 2023)
Installations of artificial structures in coastal oceans create de facto habitat for marine life. These structures encompass wide varieties of physical characteristics, reflecting their multiple, diverse purposes and creating a need to understand which characteristics maximize fish habitat. Here, we test how physical characteristics – horizontal area, vertical relief, and spatial isolation – relate to fish density from echosounder surveys over artificial structures like concrete pipes, train boxcars, and ships purposely sunk to function as reefs. Echosounder mapping of 31 artificial reef structures and associated fish across a 200 km linear length of the continental shelf of North Carolina, USA, revealed that structures with greater horizontal area and vertical relief host higher fish densities than smaller, shorter structures. Artificial structure spatial arrangement also relates to fish density, as isolated structures are generally associated with greater localized fish densities than structures closer to one another. Patterns in the relationships between fish density and reef characteristics differed for schooling fish, as there was some evidence that reefs of intermediate area exhibited higher schooling fish density. These results suggest that intentional design and spatial arrangement of marine built structures like artificial reefs relates to and can be deliberately incorporated into siting and deployment decisions to enhance their role as fish habitat.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Lower soil moisture and deep soil temperatures in thermokarst features increase old soil carbon loss after 10 years of experimental permafrost warming - Elaine F. Pegoraro; Marguerite E. Mauritz; Kiona Ogle; Christopher H. Ebert; Edward A. G. Schuur (Global Change Biology, 2021)
Almost half of the global terrestrial soil carbon (C) is stored in the northern circumpolar permafrost region, where air temperatures are increasing two times faster than the global average. As climate warms, permafrost thaws and soil organic matter becomes vulnerable to greater microbial decomposition. Long‐term soil warming of ice‐rich permafrost can result in thermokarst formation that creates variability in environmental conditions. Consequently, plant and microbial proportional contributions to ecosystem respiration may change in response to long‐term soil warming. Natural abundance δ 13 C and Δ 14 C of aboveground and belowground plant material, and of young and old soil respiration were used to inform a mixing model to partition the contribution of each source to ecosystem respiration fluxes. We employed a hierarchical Bayesian approach that incorporated gross primary productivity and environmental drivers to constrain source contributions. We found that long‐term experimental permafrost warming introduced a soil hydrology component that interacted with temperature to affect old soil C respiration. Old soil C loss was suppressed in plots with warmer deep soil temperatures because they tended to be wetter. When soil volumetric water content significantly decreased in 2018 relative to 2016 and 2017, the dominant respiration sources shifted from plant aboveground and young soil respiration to old soil respiration. The proportion of ecosystem respiration from old soil C accounted for up to 39% of ecosystem respiration and represented a 30‐fold increase compared to the wet‐year average. Our findings show that thermokarst formation may act to moderate microbial decomposition of old soil C when soil is highly saturated. However, when soil moisture decreases, a higher proportion of old soil C is vulnerable to decomposition and can become a large flux to the atmosphere. As permafrost systems continue to change with climate, we must understand the thresholds that may propel these systems from a C sink to a source.

Arsenic-containing hydrocarbons: effects on gene expression, epigenetics, and biotransformation in HepG2 cells - S. M. Müller; H. Finke; F. Ebert; J. F. Kopp; F. Schumacher; B. Kleuser; K. A. Francesconi; G. Raber; T. Schwerdtle (Archives of Toxicology, 2018)

Effects of arsenolipids on in vitro blood-brain barrier model - S. M. Müller; F. Ebert; G. Raber; S. Meyer; J. Bornhorst; S. Hüwel; H.-J. Galla; K. A. Francesconi; T. Schwerdtle (Archives of Toxicology, 2018)

Squalus bassi sp. nov., a new long‐snouted spurdog (Chondrichthyes: Squaliformes: Squalidae) from the Agulhas Bank - S. T. de. F. L. Viana; M. R. de Carvalho; D. A. Ebert (Journal of Fish Biology, 2017)
The long‐snouted African spurdog Squalus bassi sp. nov. is described based on material collected from the outer shelf and upper continental slope off South Africa and Mozambique. Squalus bassi shares with S. mitsukurii, S. montalbani, S. chloroculus, S. grahami , S. griffini, S. edmundsi , S. quasimodo and S. lobularis a large snout with prenarial length greater than distance between nostrils and upper labial furrows, dermal denticles tricuspidate and rhomboid and elevated number of vertebrae. Squalus bassi can be distinguished from all its congeners by a combination of body and fin colouration, external morphometrics, vertebral counts and shape of dermal denticles. Similar long‐snouted congeners from the Indo‐Pacific region, including S. montalbani , S. edmundsi and S. lalannei are compared in detail with the new species. This new species has been misidentified as the Japanese S. mitsukurii and the Mediterranean S. blainvillei due to the lack of comparative morphological analyses. The validity of the nominal species S. mitsukurii in the south‐eastern Atlantic Ocean and western Indian Ocean is also clarified herein, indicating it has a more restricted geographical distribution in the North Pacific Ocean.

A non-canonical role for desmoglein-2 in endothelial cells: implications for neoangiogenesis - Lisa M. Ebert; Lih Y. Tan; M. Zahied Johan; Kay Khine Myo Min; Michaelia P. Cockshell; Kate A. Parham; Kelly L. Betterman; Paceman Szeto; Samantha Boyle; Lokugan Silva; Angela Peng; YouFang Zhang; et al. (Angiogenesis, 2016)

Redescription of Scymnodon ichiharai Yano and Tanaka 1984 (Squaliformes: Somniosidae) from the western North Pacific, with comments on the definition of somniosid genera - William T. White; Diego F. B. Vaz; Hsuan-Ching Ho; David A. Ebert; Marcelo R. de Carvalho; Shannon Corrigan; Elisabeth Rochel; Murilo de Carvalho; Sho Tanaka; Gavin J. P. Naylor (Ichthyological Research, 2015)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

The SUUR protein is involved in binding of SU(VAR)3–9 and methylation of H3K9 and H3K27 in chromosomes of Drosophila melanogaster - Dmitry E. Koryakov; Matthias Walther; Anja Ebert; Sandro Lein; Igor F. Zhimulev; Gunter Reuter (Chromosome Research, 2011)

Tunicamycin inhibition of N-glycosylation of α-glucosidase from Aspergillus niveus: partial influence on biochemical properties - Tony Márcio Silva; Fausto Bruno Dos Reis Almeida; André Ricardo de Lima Damásio; Alexandre Maller; Michele Michelin; João Atílio Jorge; Ebert Seixas Hanna; Maria Cristina Roque-Barreira; Héctor F. Terenzi; Maria de Lourdes Teixeira de Moraes Poliz (Biotechnology Letters, 2010)

Induction of Early Growth Response-1 Mediates Microglia Activation In Vitro But is Dispensable In Vivo - Thomas Langmann; Stefanie Ebert; Yana Walczak; Karin Weigelt; Markus U. Ehrengruber; Thorsten Stiewe; Bernhard H. F. Weber (NeuroMolecular Medicine, 2009)

Level ground and uphill cycling ability in elite female mountain bikers and road cyclists - F. M. Impellizzeri; T. Ebert; A. Sassi; P. Menaspà; E. Rampinini; D. T. Martin (European Journal of Applied Physiology, 2007)

Comparative genetic study confirms exceptionally low genetic variation in the ancient and endangered relictual conifer, Wollemia nobilis (Araucariaceae) - Rod Peakall; Daniel Ebert; Leon J. Scott; Patricia F. Meagher; Cathy A. Offord (Molecular Ecology, 2003)
The Wollemi pine, Wollemia nobilis (Araucariaceae), was discovered in 1994 as the only extant member of the genus, previously known only from the fossil record. With fewer than 100 trees known from an inaccessible canyon in southeastern Australia, it is one of the most endangered tree species in the world. We conducted a comparative population genetic survey at allozyme, amplified fragment length polymorphism (AFLP) and simple sequence repeat (SSR) loci in W. nobilis , Araucaria cunninghamii and Agathis robusta — representatives of the two sister genera. No polymorphism was detected at 13 allozyme loci, more than 800 AFLP loci or the 20 SSR loci screened in W. nobilis . In Ag. robusta only one of 12 allozyme loci, five of 800 AFLP loci and none of the 15 SSR loci were variable. For A. cunninghamii , 10 of > 800 AFLP loci and five of 20 SSR loci were variable. Thus low genetic diversity characterizes all three species. While not ruling out the existence of genetic variation, we conclude that genetic diversity is exceptionally low in the Wollemi pine. To our knowledge this is the most extreme case known in plants. We conclude that the combination of small population effects, clonality and below‐average genetic variation in the family are probable contributing factors to the low diversity. The exceptionally low genetic diversity of the Wollemi pine, combined with its known susceptibility to exotic fungal pathogens, reinforces current management policies of strict control of access to the pines and secrecy of the pine locations.

Effect of creatine supplementation on metabolism and performance in humans during intermittent sprint cycling - J. P. Finn; T. R. Ebert; R. T. Withers; M. F. Carey; M. Mackay; J. W. Phillips; M. A. Febbraio (European Journal of Applied Physiology, 2001)

Regional impact analysis of climate change on natural and managed forests in the Federal State of Brandenburg, Germany - P. Lasch; M. Lindner; B. Ebert; M. Flechsig; F.-W. Gerstengarbe; F. Suckow; P.C. Werner (Environmental Modeling & Assessment, 1999)